FPGA Implementation On Alcohol Sensor Vehicle Immobilizer - Marjori Chu Phab (Universiti Malaysia Perlis, 2008)
Nowadays, car accident cases keep on increasing from day to day. There are many factors that had caused the accident happen. Among the major factors that caused the car accident are such as the equipment failure, poor roadway maintenance, poor roadway design and the driver behavior. But normally the driver behavior has contributed major numbers in car accident cases. The car accident has claimed many lives every year. In the urban area, normally the car accidents happen due to the drunken driver. As a result, by having this project known as FPGA Implementation on Alcohol Sensor Vehicle Immobilizer, it can keep the drunk drivers off the road. The purpose of this project is to reduce the number of accidents that caused of the drunk driver. The FPGA has been choosing in this project because it is inexpensive and easy to get. Besides that, the software development that used to design this system also simple. Actually this system had been used in others counter such as Australia and United State of America. However, the system have not been designed and implemented in our country, Malaysia yet. By designing this system, hopefully it may help our country to reduce the car accident statistics. This project will include both software (Verilog HDL) and hardware (FPGA board) development. The system has been successfully implemented on FPGA board and shown working properly. When the driver failed the alcohol test, the car cannot be started and the warning light will appeared. The driver will fail the alcohol test if their Blood Alcohol Concentration (BAC) is more than 0.05%.